PESAN-PESAN DAKWAH PADA RITUAL TURUN MANDI MASYARAKAT SUKU GAYO DI KABUPATEN BENER MERIAH PROVINSI ACEH - Sania Zahra; A. Khairuddin (Fakultas Dakwah Universitas Ibrahimy, 2023)
This research examines a da’wah message contained in the Turun Mandi ritual of the Gayo tribe in Bener Meriah Regency. The implementation of this ritual begins with taking a baby who is seven or fourteen days old to a river or a special place to be bathed in coconut water and some materials used for bathing babies. The Mandir Drop Ritual is a ritual performed before the slaughter of the aqiqah animal and the inauguration of the baby’s name which has been carried out and regulated since ancient times. This paper uses a descriptive qualitative method that uses an ethnographic approach, because it involves research on culture. The technique used in this research is interviewing community leaders who know the procedures for carrying out the Mandir Drop ritual and understand the da’wah messages contained in it. Then using observation and documentation techniques. The result is that the rituals performed by the Gayo people are not out of line with Islamic religious shari’a rules. There are da’wah messages contained. Namely the message of faith, the message of shari’ah and the moral message. All we can find in all stages of the process. Starting from a filial message to both parents, being a pious servant, making the Koran and hadith as a guide for life, being a useful child, and becoming a pious and pious generation.